Factor Structure of Organizational Commitment: Differences between U.S. and South Korean Samples - Lee, Jo Ann; Yang, Chulguen (Psychological Reports, 2005)
The current study compared the factor structures of the construct of organizational commitment between two samples of financial employees, one from the U.S. ( n = 103) and one from South Korea ( n = 109). Participants completed a 26-item questionnaire. Two factors (an affective component and a normative component) emerged for the U.S. sample; only one factor for the Koreans. Results suggest that culture should be considered when trying to assess organizational commitment.
Keywords: dept.mgt; peer-reviewed

A cross‐national analysis of affirmative action: an evolutionary psychological perspective - Yang, Chulguen; D'Souza, Geeta C.; Bapat, Ashwini S.; Colarelli, Stephen M. (Managerial and Decision Economics, 2006)
Abstract Affirmative action (AA) is a government policy permitting employers and universities to give preferential treatment to applicants from specific (e.g. racial) groups. We present a comparative analysis of AA in six countries (India, USA, Malaysia, Canada, South Africa, and Brazil) and explain similarities among these programs according to universal psychological mechanisms and variation according to cultural–historical contexts. It appears that similarities in contextual conditions (e.g. democratic government, multi‐ethnic states) interact with ancient psychological mechanisms (e.g. fairness, cheater detection, alliance tracking) to provide at least part of the motivation for the development and expansion of AA, despite its problematic consequences. Copyright © 2006 John Wiley & Sons, Ltd.
Keywords: dept.mgt; peer-reviewed

Understanding Adaptive Functions of Kinship in Immigrant Entrepreneurship: An Evolutionary Perspective - Yang, Chulguen; Colarelli, Stephen M.; Han, Kyunghee (Usiness Research Yearbook, 2008)
Keywords: dept.mgt; peer-reviewed

Immigrant Entrepreneurship from a Neo-Darwinian Co-Evolutionary Perspective - Yang, Chulguen; Colarelli, Stephen M.; Han, Kyunghee (Journal of Business Management & Change, 2008)
Keywords: dept.mgt; peer-reviewed

Asian Entrepreneurs Going Green: Cases of China and Korea - Goralski, Margaret A.; Yang, Chulguen (Usiness Research Yearbook, 2008)
Keywords: dept.mgt; peer-reviewed

Surrounded by white water: Conflicts in management sciences regarding truth and reality - Stark, Ernie; Stepanovich, Paul; Poppler, Paul; Hopkins, Pamela J. (Journal of Behavioral & Applied Management, 2008)
Keywords: dept.mgt; peer-reviewed

A Clash of Capitalisms: Foreign Shareholders and Corporate Restructuring in 1990s Japan - Ahmadjian, Christina L.; Robbins, Gregory E. (American Sociological Review, 2005)
This article examines the clash between stakeholder- and shareholder-based business systems resulting from an increase in foreign portfolio investment in the Japanese economy during the 1990s. An analysis of 1,108 firms between 1991 and 2000 shows that as foreign institutional investors, who were more interested in investment returns than in long-term relationships, replaced domestic shareholders, one fundamental pillar of Japan's stakeholder capitalism began to crack. Japanese firms began to adopt downsizing and asset divestiture, practices more characteristic of Anglo-American shareholder economies. The influence of foreigners, however, was weaker in firms more deeply embedded in the local system through close ties to domestic financial institutions and corporate groups. Thus, foreign investors were influential primarily in firms less embedded in the existing stakeholder system. This research contributes to debates on globalization and convergence of business systems, institutional change, and corporate governance systems.
Keywords: dept.mgt; peer-reviewed

The Evolution and Commercialization of Wind Power Technology. - Laird, Kenneth R. (2005)
Keywords: dept.mgt; faculty_collection; sabbatical_report

Riga, Latvia Sabbatical Leave. - Frank, Ellen J. (2003)
Keywords: dept.mgt; faculty_collection; sabbatical_report

Empower! To Win: An Action Guide to the Imperative Leadership Style of the 21st Century - Brady, Gene F. (Xlibris Corp., 2009)
Keywords: Leadership; dept.mgt

Leadership as Place - Beatty, Ellen; Page, Robert (Leadership in Place: How Academic Professionals Can Find Their Leadership Voice, 2007)
Keywords: Administration; Universities and colleges; Faculty; Educational leadership; United States; Universities and colleges; dept.aa; dept.mgt; faculty_collection

Historical Encyclopedia of American Women Entrepreneurs: 1776 to the Present - Oppedisano, Jeannette M. (Greenwood Press, 2000)
Keywords: Biography; Businesspeople; Biography; Businesswomen; Businesswomen; Encyclopedias; Encyclopedias; Businesspeople; History; United States; dept.mgt; faculty_collection

Industrial espionage: The dark side of the "Digital Age" - Nodoushani, O.; Nodoushani, P.A. (Competitiveness Review, 2002)
Amid all enthusiasm regarding the rise of the Digital Age, industrial espionage remains the dark side of the post-industrial revolution. The Federal Industrial Espionage Act of 1996 aimed at leveling the field regarding widespread cheating and stealing of intellectual properties by competitors in the marketplace. In this paper we aim at defining various forms of industrial espionage in the light of the ongoing information technology revolution. © Emerald Backfiles 2007.
Keywords: dept.mgt

Past journeys: Global lessons learned from entrepreneurial women in US history - Oppedisano, J. (International Handbook of Women and Small Business Entrepreneurship, 2005)
Keywords: dept.mgt

Learning practices: Assessment and action for organizational improvement - Hopkins, Pamela J (Academy of Management Learning and Education, 2005)
Keywords: dept.mgt

Using system dynamics to illustrate deming’s system of profound knowledge - Stepanovich, Paul L (Total Quality Management & Business Excellence, 2004)
This article presents a systems dynamics model to illustrate some of the aspects of Deming's System of Profound Knowledge. As a pedagogical tool, it would serve as a useful introduction for those new to Deming's ideas. It not only introduces the main parts of his system, but also highlights their interconnectedness. The model environment, an interactive management flight simulator, and the model content combine to provide several learning opportunities. The model uses the assumptions of regression to the mean, the 80:20 Rule, random walks, and learned helplessness to present a theory of how, managers learn to reduce quality in organizations. Those interested in exploring or teaching Deming's System can use the model as a launching point from which to explore the system further. Running the simulation provides an opportunity to identify and challenge assumptions, explore the harmful effects of tampering, examine the fundamental attribution error, develop control charts, and challenge the application of behaviourism in management.
Keywords: Deming; Pedagogy; Quality; System dynamics; dept.mgt

Process mapping in successful ERP implementations - Okrent, Michael D; Vokurka, Robert J (Industrial Management and Data Systems, 2004)
This paper discusses the six core business processes and supporting technology that are impacted by an enterprise resource planning (ERP) implementation. It begins with a brief history of the evolution of ERP and the information systems technology that enabled its development. A discussion of project implementation team preparations is followed by a description of process mapping and its significance to the success of an ERP implementation. Highlights of “As-Is” and “To-Be” process mapping and change management conclude the paper. © 2004, Emerald Group Publishing Limited
Keywords: Business processes; Costs; Enterprise resource planning; Information analysis; Information technology; Maintenance; Optimization; Planning tools; Process analysis; Process mapping; Resource management; Strategic planning; dept.mgt

Giving back: women's entrepreneurial philanthropy - Oppedisano, Jeannette (Women in Management Review, 2004)
Traditionally, the concept of entrepreneurship included a for-profit bottom line. Recently, however, researchers have begun to explore an adaptation of this model called “social entrepreneurship”; that is, creating organizations for the greater good of a community, region, nation, or the world. These entrepreneurs use money that they made or inherited to establish organizations from a missionary and visionary posture. This is an arena where women have had significant impact, yet little has been written to celebrate their contributions. The purpose of this paper is to explore the concept of such philanthropy, to suggest where this social ethic might have had its origins, and to provide samples of women who have been entrepreneurial in their social commitment. Suggestions for future research on women's entrepreneurial philanthropy will also be made. © 2004, Emerald Group Publishing Limited
Keywords: Entrepreneurialism; Philanthropy; Social action; United States of America; Women; dept.mgt

Leadership theory and practice: a “case” in point - Armandi, Barry; Oppedisano, Jeannette; Sherman, Herbert (Management Decision, 2003)
Leadership theory has little value if it cannot be applied to real world situations. A summary review of the literature on leadership theory is provided here first. A disguised real case concerning Ted Shade, a Vice-President at Galactic Chips, Inc. is then provided which describes a manager who is extremely task-oriented. The case analysis follows. It includes questions and answers which connect leadership theory to case specifics and requires learners to analyze the case using differing leadership models. © 2003, MCB UP Limited
Keywords: Leaders; Leadership; Management styles; Psychology; dept.mgt

Vitality alliance: adventures in entrepreneurial consulting - Page, Robert A (The international journal of entrepreneurship and innovation, 2003)
Keywords: dept.mgt

The strategic management of research and development - Nodoushani, Omid; Nodoushani, Patricia A (Journal of Comparative International Management, 2002)
Keywords: dept.mgt; ⛔ No DOI found

Book Review: Resource ReviewsTaking center stage: masterful public speaking using acting skills you never knew you had, by GottesmanDeb and MauroBuzz. new york, NY: berkley books, 2001. 191 pages, soft cover. - Oppedisano, Jeannette (Academy of Management Learning and Education, 2002)
Keywords: book.review; dept.mgt

Chinese students’ perceptions of women in management: will it be easier? - Frank, Ellen J (Women in Management Review, 2001)
An attitude survey was conducted with 72 management majors attending a prestigious business university in Beijing, China. The results indicate that there is still a significant “glass ceiling” effect to accepting women as they climb up the management hierarchy. The group estimated that it would take at least 32 years before equality would be reached. Women were less likely to prefer to work for a woman than for male subjects. Women were described as more incompetent, slower, weaker, more a follower-than-a-leader, more lenient, more democratic, less active, and more friendly than male managers. Women were significantly more in agreement with the idea of being both a professional and a wife. The results reflect a similar attitudinal position to US women. The conclusion is that it will not be easier for Chinese women to succeed than it is for women in theUSA. © 2001, MCB UP Limited
Keywords: Attitudes; China; Management; Managers; Perception; Women; dept.mgt

A postmodern theory of industrial democracy - Nodoushani, Omid; Nodoushani, Patricia A (Journal of Comparative International Management, 2000)
Keywords: dept.mgt; ⛔ No DOI found

The lobster tale: an exercise in critical thinking. - Stepanovich, Paul L (Journal of Management Education, 2009)
Professors in management and business are encouraged to incorporate critical thinking as an objective in their courses. "The Lobster Tale" provides an opportunity to engage students in various levels of critical thinking, ranging from a relatively superficial reading to an examination of the deeper, often hidden issues. Using the foundations of critical theory and systems theory, the story draws on economics, social theory, philosophy, and other disciplines to present a simplified version of the complexities found in our global environment. It can be used to supplement a variety of courses in the business curriculum and to encourage students to challenge not only assumptions but also conventional wisdom and, perhaps, knowledge itself. © 2009 The Author(s).
Keywords: Affirmative action; Critical theory; Critical thinking; Systems theory; Tragedy of the commons; dept.mgt

The concept of implementing effective learning assessment criteria in a virtual environment - Goralski, Margaret A (Estableciendo puentes en una economía global, Vol. 1, 2008 (Ponencias), ISBN 978-84-7356-556-1, pág. 39, 2008)
Keywords: dept.mgt; ⛔ No DOI found

Aligning health care: quality as a learning system - Goralski, Margaret A; Page, Robert A (Estableciendo puentes en una economía global, Vol. 1, 2008 (Ponencias), ISBN 978-84-7356-556-1, pág. 36, 2008)
Keywords: dept.mgt; ⛔ No DOI found

40 years of academic public psychiatry - ethnicity, mental health care disparities and culturally competent care at the connecticut mental health center - Nazroo, James; Blue, Howard C.; Añez, Luis M.; Paris, Manuel; Hawkins, Dietra; Page, Robert A. (John Wiley & Sons, Ltd, 2007)
Keywords: dept.mgt

Ethnicity, mental health care disparities and culturally competent care at the connecticut mental health center - Nazroo, James; Blue, Howard C; Anez, Luis M; Paris, Manuel; Hawkins, Dietra; Page, Robert A (40 Years of Academic Public Psychiatry, 2007)
Keywords: Community-based prevention efforts; Deinstitutionalization impact; Housing and employment discrimination; Psychotic disorders and unrelenting affective disorders; Third psychiatric revolution; dept.mgt

Role modeling as a pedagogical strategy in entrepreneurship education for women and girls: An interactive model of transformational learning - Oppedisano, Jeannette; Laird, Kenneth R (New England Journal of Entrepreneurship, 2006)
This article presents a pedagogical model that utilizes students as primary researchers in the identification, interviewing, and then reporting on women entrepreneurs as a major component of a multidisciplinary entrepreneurship course. The purpose of the course is to attract students who may not be familiar with the entrepreneurship concept itself, the role of women in such economic ventures, or the possibilities for people like themselves in such a career avenue. Students are exposed to the accomplishments of women entrepreneurs throughout U.S. history in the broad categories of agriculture and mining; construction; communication; manufacturing; service (both for profit and not-for-profit); transportation; and wholesale and retail trade. This content experience is then enhanced by the studentsʼ own direct interaction with and interviewing of women entrepreneurs. The implementation, potential outcomes, and possible adaptations of the course are described, and this transformational learning process model is illustrated. © Published by DigitalCommons©SHU, 2006.
Keywords: dept.mgt